Colonic or ileocecocolic volvulus in 13 dogs (2005‐2016). Issue 6 (20th May 2017) - Plavec, Tanja; Rupp, Stefan; Kessler, Martin
Abstract: Objective: To describe the clinical and clinicopathological features of colonic or ileocecocolic volvulus (CV/ICV) in dogs. Study design: Retrospective case series. Animals: Thirteen dogs with surgically confirmed CV/ICV. Methods: Medical records were reviewed for signalment, medical history, clinical signs, laboratory data, radiographic findings, treatment, and outcome. Results: All cases consisted of large‐breed dogs (median weight 37.1 kg, range, 22.7‐58.5 kg), 8 of these male (6 intact). The most common clinical signs included vomiting, depression, inappetence, and diarrhea with or without tenesmus. All cases presented in shock with abdominal distension, abdominal pain, or both. Dogs were treated for shock and operated immediately after a presumptive diagnosis was based on clinical and radiographic examinations. Three dogs were euthanatized during surgery, 10 dogs were discharged live from the hospital, 9 of these were alive at follow‐up 6 to 70 months (median 24 months) after surgery. Conclusion: CV and ICV are rare disorders that seem to carry a better prognosis than mesenteric volvulus. Immediate laparotomy is recommended in suspected cases and the prognosis is fair.